Pathway decisions during the student-athlete transition out of university in the United Kingdom. Issue 4 (4th July 2022) - Vickers, Emma; Morris, Robert
Abstract: The student-athlete transition out of university requires athletes to make important decisions regarding their future. However, there is no research that focuses on the pathways that athletes take when they leave university and the factors that underpin athletes' decisions. The current study explored the pathways athletes take when they leave university in the United Kingdom (UK), and their reasons for taking these specific routes. Eleven elite UK former and current university student-athletes ( M age = 21.4) from different sports were interviewed. Eight university stakeholders (e.g., head coaches, lifestyle advisor, performance sport manger) took part in a focus group. Data were thematically analyzed. Results suggest that athletes take four different pathways following university: (1) advancing onto a postgraduate education and elite sport pathway, (2) full-time sport pathway, (3) sport and work pathway, and (4) dropping out of sport and moving onto an alternative pathway. There were multiple factors that led athletes to taking each pathway. These included a desire to qualify for the next Olympic Games, having an education "safety net, " goal of advancing onto a funded sport programme, and limited work-sport dual career opportunities. This article advances previous work in athlete transitions and athlete career pathways, focusing specifically on a key career transition point for UK athletes. Support providers could use the findings to help athletes critically reflect on their motivations and future goals and come to a decision around what their most suitable pathway should be. Lay summary : We explored the experiences of UK student-athletes as they left university, including the factors that influence their decisions around what they do. Student-athletes were found to take four different routes and had different motives and reasons why they took the route that they did. Implications for Practice: Practitioners should support athletes to critically reflect on their motivations and future goals when they are about to complete university and come to a decision around what their most suitable pathway should be. Risks of taking a make or break year as a full-time athlete after university without funding secured should be communicated to athletes. National governing bodies (NGBs) should consider more carefully how they can incorporate dual career opportunities into their centralized programmes. Universities are advised to offer postgraduate athlete support programmes. Parents, NGBs, and university stakeholders should use a collaborative approach to support the athlete to critically examine their opportunities post-university.